Motivators, Barriers and Concerns in Adoption of Electronic Filing System: Survey Evidence from Malaysian Professional Accountants - Ming-Ling Lai; Kwai-Fatt Choong (American Journal of Applied Sciences, 2010)
Worldwide, electronic filing (e-filing) system and its' adoption has attracted much attention, however, scholarly study on accounting professionals' acceptance of e-filing system is scant. Approach: This study aimed (i) to examine factors that motivated professional accountants to use e-filing (ii) to solicit their usage experience and (iii) to assess the barriers to adoption and other compliance considerations. The questionnaire survey was administered on 700 professionals from tax practice and commercial sectors who attended “Budget 2008” Tax Seminars, organized by the Malaysian Institute of Accountants in Peninsular Malaysia. In total, 456 usable responses from accounting and tax professionals were collected and analyzed. Results: The survey found out of 456 respondents, just 23.7% had used e-filing in 2007 to file personal tax return forms. Majority of the e-filers opted to use e-filing for the sake of convenience (55.8%), in faith to get faster tax refund (16.8%) and speed of filing (15.9%). For those who did not use e-filing, the key impediments were concerned over the security and did not trust of e-filing system. Some (4.8%) were unable to access to the e-filing website. Overall, just 26.1% of the professionals surveyed had confidence in the IRBM in managing the e-filing system successfully. Majority (41.2%) thought that `speedy tax refund' to be the most desirable incentive to motivate individuals to use e-filing. Conclusion: As the IRBM is counting on professional accountants to promote the usage of e-filing system, this study provided important insights to the IRBM to developing marketing and business strategies to motivate professional accountant in business to use e-filing in order to accelerate the diffusion of e-filing system in a developing country like Malaysia.
Keywords: H2; 650; Electronic tax filing; motivators; barriers; professional accountant; Malaysia